2023
DOI: 10.1037/sah0000268
|View full text |Cite
|
Sign up to set email alerts
|

Weight- and health-focused conversations in racially/ethnically diverse households with and without a child with overweight/obesity.

Abstract: Studies indicate parent conversations focused on child weight, shape, or size are associated with unhealthy child weight and weight-related behaviors, whereas health-focused conversations are not. Little research has examined what these types of conversations sound like, how parents respond to them, and whether households with or without a child with overweight/obesity approach these conversations differently. This study used qualitative data to identify the weight-and health-focused conversations occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Typically, evidence points to higher levels of parental weight communication with youth who have higher body mass index (BMI) 2,6,7 . However, other evidence indicates that parents engage in weight‐focused conversations with children across diverse body weights and sizes, 8 suggesting that weight communication occurs in families irrespective of weight status.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, evidence points to higher levels of parental weight communication with youth who have higher body mass index (BMI) 2,6,7 . However, other evidence indicates that parents engage in weight‐focused conversations with children across diverse body weights and sizes, 8 suggesting that weight communication occurs in families irrespective of weight status.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly little research attention has focused on why parents choose to engage in, or avoid, talking about weight with their children. To date, insights about parental motivations come from primarily qualitative evidence 8,18–22 . For example, findings from interviews with primarily Black/African American parents ( N = 47%, 90% female) found that parents talked to their child(ren) about weight because of a health professional's concern about their child's health; their own parental concerns; or to ‘strengthen their child's skin’ so that their child would not be as upset by being teased about their weight from others 20 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations